LOS ARMADILLOS (MAMMALIA, DASYPODIDAE) DE LA TOMA (PARTIDO DE CORONEL PRINGLES) Y OTROS SITIOS ARQUEOLOGICOS DE LA PROVINCIA DE BUENOS AIRES. CONSIDERACIONES PALEOAMBIENTALES (Ameghiniana, 2013)
ARMADILLOS (MAMMALIA, DASYPODIDAE) FROM LA TOMA (CORONEL PRINGLES COUNTY) AND OTHER ARCHAEOLOGICAL SITES FROM BUENOS AIRES PROVINCE. PALEOENVIRONMENTAL CONSIDERATIONS.Dasypodidae remains from La Toma archaeological site (Coronel Pringles County, Buenos Aires Province) were analized. The material is grouped in two levels: the lower is characterized by the presence of Chaetophractus villosus and Zaedyus cf. Z. pichiy, and the upper with Dasypus sp. cf. D. hybridus-D. septemcinctus associated to the other two species. Information from other archaeological sites of the Buenos Aires Province was incorporated. A paleoenvironmental sequence is proposed for the lapse late Pleistocene Holocene: 1) Generalized arid or semiarid conditions that last until partly the late Holocene; 2) A transition toward more humid and warm conditions between 1000 and 1700 years BP; 3) Temperate and humid conditions, similar to the present ones, registered close to the European Conquest (XVI century) and after it. A description of the scutes morphology of the different species is provided.